1979
DOI: 10.1039/p29790000325
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of solvent effects on the Menshutkin reaction between 1,4-diazabicyclo[2.2.2]octane and 2-chloroethylbenzene, 2-bromoethylbenzene, and 2-iodoethylbenzene. Part 2. Mixed solvents

Abstract: We have elucidated by kinetic studies the complex behaviour of the protic compounds at low concentration in various solvents for the Menshutkin quaternation reaction between 1,4-diazabicyclo[2.2.2]octane and 2-chloroethyl-, 2-bromoethyl-, and 2-iodoethyl-benzene. The variation of the reaction rate is interpreted on the basis of non-specific physical and specific chemical effects. The specific effects arise from the formation of hydrogen bonded complexes between the protic compound and the amine, the halide, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Higher molecular masses of the polymers that were attained when acetonitrile was replaced with nitromethane should probably be attrib uted to a marked acidity of the methyl group of nitromethane; as a consequence, the electrophilic catalysis of the alkylation of oxazoline occurs. A simi lar increase in the rate constant of alkylation (by a fac tor of 2) was observed for the reaction of quarterniza tion of amines when acetonitrile was replaced with nitromethane [20], an effect that was rationalized by the proton donor properties of nitromethane.…”
Section: Resultsmentioning
confidence: 90%
“…Higher molecular masses of the polymers that were attained when acetonitrile was replaced with nitromethane should probably be attrib uted to a marked acidity of the methyl group of nitromethane; as a consequence, the electrophilic catalysis of the alkylation of oxazoline occurs. A simi lar increase in the rate constant of alkylation (by a fac tor of 2) was observed for the reaction of quarterniza tion of amines when acetonitrile was replaced with nitromethane [20], an effect that was rationalized by the proton donor properties of nitromethane.…”
Section: Resultsmentioning
confidence: 90%
“…The conventional TST expression cannot account for nonidealities such as high pressure and solvent effects, which are clearly important to the Menshutkin reaction. Kramers extended the theory by modeling a chemical reaction as a classical particle of mass, m , moving in a one-dimensional asymmetric double-well potential U ( x ). , The remaining degrees of freedom of the surrounding molecules were incorporated as a heat bath at temperature T , which influences the reaction coordinate through a fluctuating force ξ­( t ) (Brownian motion) and a damping force − mγx ̇, where γ represents a constant damping rate (friction). For moderate-to-strong friction, he obtained the following result for the rate constant: where ω b 2 is related to the curvature of the potential at the position of the transition state. , The term κ is called the transmission coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…Of the many reactions of interest, the Menshutkin S N 2 reaction is notable for its use in the study of solvent and medium effects on chemical reactivity. This special class of S N 2 reactions involves the alkylation of a formally sp 2 or sp 3 hybridized nitrogen atom where Nu and L represent the nucleophile (amine) and leaving group, respectively. The nucleophilic attack occurs on the opposite side of the substrate (RL) relative to the leaving group, resulting in the typical S N 2 transition state consisting of a 5-coordinated carbon atom .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,54 The Menshutkin reaction is also a characteristic example for studying the effect of solvation on reactions 53 since it displays pronounced solvent effects on activation barriers. 54,56,57 Experimental studies have shown a decrease in the activation energy depending on the polarity of the solvent. The experimentally reported activation barrier for Pyr+MeBr in methanol is 22.5 kcal/mol which is 3.1 and 5.1 kcal/mol lower compared with apolar cyclohexane and di-n-butyl ether.…”
Section: Introductionmentioning
confidence: 99%